Cytarabine-Induced Corneal Toxicity: Clinical Features and Relief of Symptoms with Loteprednol Etabonate 0.5% in Two Patients - Gökçen Özcan; Ömür Özlenen Uçakhan (Türk Oftalmoloji Dergisi, 2021)

(untitled)
We report two patients who developed toxic keratopathy following high-dose cytarabine chemotherapy and whose symptoms resolved following topical loteprednol etabonate 0.5% treatment. A 25-year-old woman and a 26-year-old man with acute myeloid leukemia were referred to our department with symptoms of ocular discomfort, photophobia, and blurred vision after consolidation chemotherapy. Central corneal epithelial microcysts were observed bilaterally in both patients, and in vivo confocal microscopy showed highly reflective disseminated granular and irregular intraepithelial opacities, mainly in the basal epithelial layers. Loteprednol etabonate 0.5% relieved both patients’ symptoms in less than a week, and the microcysts disappeared in 2 to 3 weeks of treatment. Although there is no standardized treatment protocol for cytarabine-induced corneal toxicity, dexamethasone 0.1% and prednisolone phosphate 1.0% were reported to be effective in the resolution of discomfort and symptoms. In the two patients we report herein, loteprednol etabonate 0.5% four times daily was also effective in suppressing the symptoms.